Landscape as a soft locational factor: The development of guidelines, targets and project-based proposals for action to secure and develop aesthetic landscape qualities - Mayer, Verena; Schlick, Mark; Groeger, Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
This article deals with the conservation and development of the aesthetic qualities of the largely man-made landscapes of the Rhine-Neckar-Palatinate conurbation. Proceeding through a series of stages of intensive analysis, the authors develop a number of innovative concepts for restoring to the landscape of this area some sense of identity as a means of enhancing the living and working environment experienced by the people who live there. Landscape quality is steadily gaining in importance as a soft locational factor. The present study puts forward a number of approaches suitable for giving this trend the recognition it warrants, for example within the framework of a Regional Landscape Park; it also underscores the need for immediate action in order to secure what open spaces still exist within this conurbation and to develop them in a manner which is aesthetically pleasing.